The crystal structure of bis[4-bromo-2-(1H-pyrazol-3-yl) phenolato-κ2N,O] copper(II), C18H12Br2CuN4O2 - Jaćimović Željko K.; Tomić Zoran D.; Giester Gerald; Libowitzky Eugen; Ajanović Atifa; Kosović Milica (Zeitschrift für Kristallographie - New Crystal Structures, 2021)
C18H12Br2CuN4O2, monoclinic, P21/c (no. 14), a = 11.5165(11) Å, b = 5.4369(5) Å, c = 14.4872(14) Å, V = 873.52(14) Å3, Z = 2, Rgt(F) = 0.0232, wRref(F2) = 0.0559, T = 200 K.